Lower temperature (27°C) Decreased Total Motile Sperm Count but not DNA Fragmentation Index in Sperm Preparation with Swim-Up Method in Male Infertility (Bangladesh Journal of Medical Science, 2025)
Background Temperature has a complex impact and is likely to influence the early stages of spermatogenesis. This study aimed to determine the effect of differential temperature in sperm preparation using the swim-up method on total motile sperm count (TMSC) and DNA fragmentation index (DFI) of male infertility.Methods This experimental study recruited 37 infertile male patients who attended the Sekar Fertility Clinic, Dr. Moewardi General Hospital, in November 2020, and we added more participants in December 2022. Before collecting semen samples, all infertile males signed informed consent. The collected sample is divided into 1 ml for sperm preparation in groups A (27°C) and B (37°C). The Wilcoxon test analyzed the data; p